Young People in The Labour Market (Past, Present, Future): Sebuah Review - Ina Yosia Wijaya; Viridian Mangsah Puspandara (Jurnal Studi Pemuda, 2022)
Tinjauan Buku "Young People in The Labour Market: Past, Present, Future"